2020
DOI: 10.1200/jgo.19.00257
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Screening in Oral, Breast, and Cervical Cancer in the Population of the Northeast Region of India

Abstract: PURPOSE The burden of cancer is increasing globally, with poor outcomes in terms of morbidity and mortality in patients, especially in low- and middle-income countries. Lack of awareness of the risk factors, symptoms, and signs of common cancers in addition to inadequate cancer prevention programs at the community level are a major hindrance to the early detection of cancer. METHODS A cross-sectional study was conducted in the North East Region (NER) of India, with a sample population of 1,400 participants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 15 publications
(19 reference statements)
0
30
1
Order By: Relevance
“…Men were having less knowledge about breast cancer than women that is consistent with earlier study. (1) This difference may also be due to the fact that breast cancer is not affecting men directly so much, (4) so they would have shown less interest in breast cancer information available on social media. Furthermore, this study finding suggests that a very good percentage of the participants were married (87%) that might have resulted in higher knowledge of breast cancer coming through social media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men were having less knowledge about breast cancer than women that is consistent with earlier study. (1) This difference may also be due to the fact that breast cancer is not affecting men directly so much, (4) so they would have shown less interest in breast cancer information available on social media. Furthermore, this study finding suggests that a very good percentage of the participants were married (87%) that might have resulted in higher knowledge of breast cancer coming through social media.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a global burden (1) and it is the most common cancer among women of India. (2) Poor level of awareness of the disease is one factor among others causing advance diagnosis and eventually death (2,3) especially in developing countries like India.…”
Section: Introductionmentioning
confidence: 99%
“…Computed IPCL pattern analysis of oral lesions. Generation of Raman Spectroscopy subjected to computer analysis [7]. Microscopy *Histopathology *Cytopathology…”
Section: Detection Methodsmentioning
confidence: 99%
“…More than 70% deaths due to cancer occurred in productive age of individuals (30-69years). Age standardized incidence rate for all cancers is 94 per 100,000 individuals [6,7]. Incidence of OSCC in India is higher compared to the western world due to regional variations and pattern of habits.…”
Section: Introductionmentioning
confidence: 99%
“…Older women in their 50s said they were uncomfortable allowing young nurses to perform cervical examination. A study undertaken in the northeast region among 1400 participants showed that only 31% of women had heard about cervical cancer and, among those, only about 55% knew the appropriate age for screening; screening intake was negligible 32 …”
Section: Cervical Cancer Screening In Indiamentioning
confidence: 99%